Parent perspectives and psychosocial needs 2 years following child critical injury: A qualitative inquiry. Issue 5 (May 2020) - Foster, Kim; Van, Connie; McCloughen, Andrea; Mitchell, Rebecca; Young, Alexandra; Curtis, Kate
Highlights: This is the first study to report on parent psychosocial wellbeing and resilience two years following child injury and the findings provide new knowledge in the field. We provide strategies and resources used by parents to support their resilience. Parents' experiences and needs are closely related to their child's physical and emotional recovery, and the support services available to them. Where a child's physical recovery was limited or slow in progress, greater attention was needed to support emotional recovery for both the child and parent. Getting back to a 'normal' life and returning to routine as soon as possible was important for their own and the family's wellbeing. These parents made a conscious effort to do the things they used to do before their child's injury. A long-term social work family case management approach is required to ensure continuity of care, integration of support and early targeted intervention to prevent long-term adverse outcomes. Abstract: Introduction: To provide effective care and promote wellbeing and positive outcomes for parents and families following paediatric critical injury there is a need to understand parent experiences and psychosocial support needs. This study explores parent experiences two years following their child's critical injury. Methods: This multi-centre study used an interpretive qualitative design. Parent participants were recruited from four paediatric hospitals in Australia. Semi-structured interviews were audio recorded and transcribed verbatim. Qualitative data were thematically analysed and managed using NVivo 11. Results: Twenty-two parents participated. Three themes were identified through analysis: Recovering from child injury; Managing the emotional impact of child injury; Being resilient and finding ways to adapt. Conclusions: A long-term dedicated trauma family support role is required to ensure continuity of care, integration of support and early targeted intervention to prevent long-term adverse outcomes for critically injured children and their families. Early and ongoing psychosocial intervention would help strengthen parental adaptation and address families' psychosocial support needs following child injury.